On the ridge of instability in ferrofluidic Couette flow via alternating magnetic field - Sebastian Altmeyer (Nature Portfolio, 2021)
Abstract There is a huge number of natural and industrial flows, which are subjected to time-dependent boundary conditions. The flow of a magnetic fluid under the influence of temporal modulations is such an example. Here, we perform numerical simulations of ferrofluidic Couette flow subject to time-periodic modulation (with frequency $$Ω _H$$ Ω H ) in a spatially homogeneous magnetic field and report how such a modulation can lead to a significant Reynolds number Re enhancement. Consider a modified Niklas approximation we explain the relation between modulation amplitude, driving frequency and stabilization effect. From this, we describe the system response around the primary instability to be sensitive/critical by an alternating field. We detected that such an alternating field provides an easy and in particular accurate controllable key parameter to trigger the system to change from subcritical to supercritical and vice versa. Our findings provide a framework to study other types of magnetic flows driven by time-dependent forcing.